Pengalaman Sosial Perempuan Berwirausaha di Bidang perdagangan Teknologi: Studi Kasus Pedagang di Hitech Mall Surabaya - Jaelani, Abdul Qodir; Listyani, Refti Handini; Ridwan, Ahmad (The Center for Gender and Children Studies, the Institute for Research and Communing Service, State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2025)
This study aims to describe the social experiences of women entrepreneurs in the technology trade sector, particularly in facing social interactions influenced by gender bias, domestic stereotypes, ethnic discrimination, and environmental stigma. Using Alfred Schutz's phenomenological qualitative approach, this study explores the subjective meanings of the actions of female traders through in-depth interviews with five informants whose identities have been concealed. The results show that female traders face structural inequality in the form of professional belittlement, social exclusion, price injustice, and the spread of slander that affects business continuity. These findings also confirm that women's actions are shaped by because motives that stem from previous discriminatory experiences, and in-order-to motives that reflect their goals in maintaining professional identity and business stability. Overall, this study concludes that the technology trading space is not only an economic arena, but also a social arena where women negotiate meaning, develop survival strategies, and fight for self-legitimacy in an environment that is not yet fully gender-equal.